2004
DOI: 10.1177/0007650304265956
|View full text |Cite
|
Sign up to set email alerts
|

An Inductive Model of Collaboration From the Stakeholder’s Perspective

Abstract: This work emerged from funded research examining collaboration among stakeholder organizations present at three U.S. nuclear weapons complex sites. The authors examine issues such as how and why stakeholder groups form collaborative alliances when dealing with the target organization, what leaders of stakeholder organizations actually think about when collaborating to deal with the target organization, and what outcomes result from the collaboration process. Drawing on stakeholder theory and research in intero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 59 publications
3
56
0
Order By: Relevance
“…On the other hand, stakeholders may also engage in behaviours aimed at supporting the interests of the firm (Harrison et al 2010;Hayibor 2012). For these reasons, as noted by Butterfield et al (2004), the overall conclusion of the instrumental branch of stakeholder theory is that managing stakeholder interests is absolutely critical for the well-being of the firm's bottom line (Berman et al 1999;Jensen 2002;Waddock and Graves 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, stakeholders may also engage in behaviours aimed at supporting the interests of the firm (Harrison et al 2010;Hayibor 2012). For these reasons, as noted by Butterfield et al (2004), the overall conclusion of the instrumental branch of stakeholder theory is that managing stakeholder interests is absolutely critical for the well-being of the firm's bottom line (Berman et al 1999;Jensen 2002;Waddock and Graves 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Berman et al 1999;Ogden and Watson 1999). Butterfield et al (2004) note that despite scholarly calls for development of stakeholder theory from the stakeholder's perspective, very little work from this viewpoint has occurred. Indeed, Laplume et al (2008) found that only 12 % of articles concerning stakeholder theory were devoted to questions about stakeholder perspectives or behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…As previously suggested by Austin, (2000), and Butterfi eld et al (2004), in NZ, it could be argued that collaborations are emerging because businesses are increasingly re-examining their traditional philanthropic practices and seeking new strategies of engagement with their communities that will have greater corporate relevance and higher social impact. It is also signifi cant to point out that business partners in NZ have rarely used their collaboration with nonprofi ts to enhance public perceptions which is in stark contrast with their counterparts in many developed countries.…”
Section: Evidence From Nzmentioning
confidence: 96%
“…First, I broke down the data for the appearance of patterns and themes. Second, I analyzed and open-coded the resulted categories into "thought units" (Butterfield, Reed, & Lemak, 2004). I applied a coding-recoding strategy to my analysis to make sure my findings are dependable.…”
Section: Data Analysis Proceduresmentioning
confidence: 99%